TREATMENT OF NERVES INJURIES ASSOCIATED WITH PEDIATRIC SUPRACONDYLAR HUMERAL FRACTURES-OUR EXPERIENCE - Todorovikj, Lazar; Kamiloski, Marjan; Memeti, Shaban; Cokleska, Natalija; Mikjunovikj Ljubica; Racaj Anila (SHMSHM - AAMD, 2020)
Background: Supracondylar fractures of the humerus are the most common type of elbow fracture in children. Nerve injury is the most common complication. Our study aims to determine the risk of traumatic nerve injury associated with supracondylar fracture, to compare the risk in flexion-type compared with the extension type fractures, and to note any iatrogenic nerve injury after pin fixation. Material and methods: The target group in this study is consisting of pediatric population (90 cases) presented with a displaced supracondylar fracture of the humerus (Gartland type II and III). All patients were treated at the University Clinic of Pediatric surgery-Skopje in the period of time from 2010 to 2020. The children were 2 to 14 years old. All of them were evaluated for nerve injury before and after the operation in order to determine if the nerve injury is traumatic or iatrogenic. Type of fracture, flexion or extension type was noticed. Results: According to the data from 90 children treated for displaced supracondylar fracture of the humerus, traumatic nerve injury occurred in 9 patients (10%). 4 (44,4%) of the referred nerve injuries involved the ulnar nerve. All ulnar nerve injuries were result of a flexion type supracondylar fracture. 3 (33,3%) injuries involve the median nerve. All of them were result of an extension type of supracondylar fracture. The anterior interosseous nerve, as a branch of a median nerve was injured in all 3 cases. 2 (22.2%) were injuries of the radial nerve, all of them as a result of an extension type of supracondylar fracture. Conclusions: According to our results, among all nerve injury associated with supracondylarar fractures, ulnar nerve injury predominates. Ulnar neuropathy occurred most frequently in flexion-type injuries. All 9 neuropathies were directly related to the injury itself and were noted at the time of admission. Spontaneous neurological recovery occurred in all 9 patients at a mean of 7.7 months (3 to 15) after injury.